Narratives of subjective (re)-building in the reality show What Not to Wear - Silva, Simone Bueno da (2012)
The objective is to analyze the structure of narratives of subjective rebuilding in the reality show What Not to Wear. The scope in this case is to investigate, under the greimasian discursive semiotics beliefs, how this television broadcast, a current phenomenon, creates its storyline, the expressive resources it uses and then verify the sensibility and interaction raised and how they become systems of an underlying presence in building patterns within the construction of the contemporary subjective narrative.